Increasing Students' Vocabulary Mastery by Using Mind Mapping - Herman; Muliaty Ibrahim; Muhamad Yahrif (FKIP, Universitas Lakidende Unaaha, 2022)
This research aimed to increase students’ vocabulary mastery by using mind mapping. The researcher gave material about vocabulary by using mind mapping via WhatsApp group (online learning). The subject of this research was class VII C which consists of 25 students at SMP Tut Wuri Handayani Makassar, the academic year 2020/2021. The researcher used the classroom action research method in two cycles; each cycle consists of planning, action, observation, and reflection. The instrument used interview, field note, vocabulary test, and documentation. The result of this research showed the increase of the student's vocabulary mastery by using the mind mapping technique from cycle 1 to cycle 2. It can be seen from the average test calculating in cycle I was 70.48 (11 students or 44% got completeness) and cycle II was 80.6 (18 students or 72% got completeness). This indicates that by using mind mapping, students’ vocabulary mastery can be increase significantly.